A Comparative Perspective on Long-Term Care Systems - Rainer Kotschy; David E. Bloom (Institute of Labor Economics (IZA), 2022)
This paper investigates challenges of aging for long-term care. Our analysis proceeds in three steps. In the first step, we estimate the prospective care demand for 30 developed countries based on projected aging and disabilities among the elderly. In the second step, we outline challenges for care systems with respect to shortages of care workers, increasing skill requirements for care workers, barriers to universal and equitable access to care, and cost containment subject to adequate care quality. In the third step, we identify solutions for these challenges by comparing the care systems of Germany, Israel, Japan, the Netherlands, and South Korea.
Keywords: J11; I18; I38; H51; H75; 330; long-term care insurance; population aging; care demand; ADL; IADL